Project Initiated Citizen Forums at Grassroots in Bangladesh: Lessons Learned (Global Journal of Human-Social Science, 2016)
Bangladesh is one of the densely populated countries which recently graduated to lower-middle income country in the world. A number of donor-funded nongovernment organizations are working at grassroots for socioeconomic development since long. This article aims to diffuse major learning of project-led civic groups at grassroots level. It describes about engagement between state guardians and grassroots civil society in Bangladesh. A mixed method, applying both qualitative and quantitative methodologies was adopted to conduct fieldwork. A total of 130 respondents from civil society groups were surveyed for data collection. This paper finds that, by project interventions, citizens of remote coastal areas involved Members of Parliament (MPs), ministry, media and key actors through research, interactive policy dialogue, and networking. They have interest and significant knowledge about lives & livelihoods and promoting public policy. However, organizational sustainability of such civil society groups is fragile in nature due to short duration and stereotype guidance from project. This paper concludes that project initiated civil society literally failed to achieve its main advocacy goal, that is, to promote agreed coastal policy though it improves visionary zeal and capacity among citizens. Short duration of project and political unrest are major hindering factors for institutional sustainability of grassroots civil society.
Keywords: civil society; coastal communities; parliament; public policy; well-beings